Prevalence of anaemia and low intake of dietary nutrients in pregnant women living in rural and urban areas in the Ashanti region of Ghana - Ayensu, Jessica; Annan, Reginald; Lutterodt, Herman; Edusei, Anthony; Peng, Loh Su (Public Library of Science (PLoS), 2020)
Background: Anaemia remains a major cause of morbidity and mortality among women and children worldwide. Because deficiencies in essential micronutrients such as iron, folate and vitamin B12 prior to and during gestation increase a woman’s risk of being anaemic, adequate dietary intake of such nutrients is vital during this important phase in life. However, information on the dietary micronutrient intakes of pregnant women in Ghana, particularly of those resident in rural areas is scanty. Thus, this study aimed to assess anaemia prevalence and dietary micronutrient intakes in pregnant women in urban and rural areas in Ghana. Methods: A comparative cross sectional study design involving 379 pregnant women was used to assess the prevalence of anaemia and low intake of dietary nutrients in pregnant women living in rural and urban areas in the Ashanti region of Ghana. Anaemia status and mid upper arm circumference (MUAC) were used as proxy for maternal nutritional status. Haemoglobin measurements were used to determine anaemia prevalence and the dietary diversity of the women were determined with a 24-hour dietary recall and a food frequency questionnaire. Results:Overall, anaemia was present in 56.5% of the study population. Anaemia prevalence was higher among rural residents than urban dwellers. Majority of the respondents had inadequate intakes of iron, zinc, folate, calcium and vitamin A. The mean dietary diversity score (DDS) of the study population from the first 24-hour recall was 3.81 ± 0.7. Of the 379 women, 28.8% met the minimum dietary diversity for women (MDD-W). The independent predictors of haemoglobin concentration were, gestational age, maternal age and dietary diversity score. Such that respondents with low DDS were more likely to be anaemic than those with high DDS (OR = 1.795, p = 0.022, 95% CI: 1.086 to 2.967). Conclusions: A large percentage of pregnant women still have insufficient dietary intakes of essential nutrients required to support the nutritional demands during pregnancy. Particularly, pregnant women resident in rural areas require interventions such as nutrition education on the selection and preparation of diversified meals to mitigate the effects of undernutrition.